Zinc chalcogenide nanostructures: synthesis methodologies and applications—a review - Chatterjee, Anindita; Kumar, G. Kiran; Roymahapatra, Gourisankar; Das, Himadri Sekhar; Jaishree, G.; Rao, T. Siva (Frontiers in Nanotechnology, 2024)
Zinc chalcogenide nanostructures are an important class of non-toxic nanomaterials due to their biocompatible nature, surface flexibility, high degree of crystallinity, and high photoluminescence efficiency that makes them applicable in solar cells biosensors, photocatalysts, LEDs, and electroluminescence materials. There are various methods for synthesizing zinc chalcogenides, including ZnS, ZnSe, and ZnTe, through colloidal, hydrothermal, solvothermal, microwave, and core shell synthesis to prepare highly luminescent material for drug delivery and biomedical applications. The main focus of this review is to explore various synthetic approaches to tune the morphology, size, and surface properties of zinc-based chalcogenide nanostructures, revealing their potential as biocompatible quantum dots. Despite their advantages, zinc chalcogenides also have certain drawbacks, such as low mechanical strength, limited bandgap tunability, and less thermal stability, that can point the way for future research. Thus, this review may prove beneficial for developing and designing more advanced nanomaterials based on existing knowledge, protocols, and strategies.